“If you weren't connected to the Internet, you were not alive”: experience of using social technology during COVID-19 in adults 50+ - Ling, Katrina; Langlois, Danielle; Preusse, Harrison; Rheman, Jennifer M.; Parson, Danya; Kuballa, Sarah; Simecek, Martin; Tsui, Katherine M.; Fraune, Marlena R. (Frontiers in Public Health, 2023)
Loneliness and social isolation reduce physical and mental well-being. Older adults are particularly prone to social isolation due to decreased connection with previous social networks such as at workplaces. Social technology can decrease loneliness and improve well-being. The COVID-19 pandemic prompted quarantine and social distancing for many people, creating a context of widespread social isolation. In the current study, we interviewed middle-aged and older adults’ (n = 20) about their use of social technology when social isolation was common: during the early part of the pandemic while social isolation and masking were still required in the United States, between August 2020 and June 2021.We analyzed the data using three-phase coding. We compare our results against Nowland et al.’s (1) model of the bidirectional and dynamic relationship between social internet use and loneliness. We found that during the COVID-19 pandemic, our participants experienced decreased social interaction and moved toward online interaction. Participant use of social technology supported the stimulation hypothesis – that is, they used it to maintain existing relationships and social connection. The findings also add novel evidence that the stimulation hypothesis endures for older adults during enforced isolation (in this case due to the COVID-19 pandemic). Based on our data, we also propose adding the presence or realism of connection via social technology as a main factor to the model and engaging with construal level theory of social presence to fill in critical variables of this relationship. We further find that digital exclusion acts as a barrier to obtaining benefits from stimulation via social technology and recommend that further research examined digital exclusion in relation to Nowland et al.’s (1) model. Finally, we discuss recommendations for improving social technology to benefit middle-aged and older adults.